2022
DOI: 10.1038/s41598-022-12602-w
|View full text |Cite
|
Sign up to set email alerts
|

Determination of sub-ps lattice dynamics in FeRh thin films

Abstract: Understanding the ultrashort time scale structural dynamics of the FeRh metamagnetic phase transition is a key element in developing a complete explanation of the mechanism driving the evolution from an antiferromagnetic to ferromagnetic state. Using an X-ray free electron laser we determine, with sub-ps time resolution, the time evolution of the (–101) lattice diffraction peak following excitation using a 35 fs laser pulse. The dynamics at higher laser fluence indicates the existence of a transient lattice st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…A substantial distribution in nanograin size, porosity, and potential dispersion around the equiatomic composition could contribute to the observed broad thermal hysteresis. Interestingly, despite the nanogranular microstructure of the presently characterised thick film, the magnetic field dependence of the transition temperature closely resembles that observed in continuous FeRh films 23 and wires, 13 i.e. nearly linear with a slope of −9.1 K/T as seen in Fig.…”
Section: Chemical Composition and Crystallographysupporting
confidence: 55%
See 2 more Smart Citations
“…A substantial distribution in nanograin size, porosity, and potential dispersion around the equiatomic composition could contribute to the observed broad thermal hysteresis. Interestingly, despite the nanogranular microstructure of the presently characterised thick film, the magnetic field dependence of the transition temperature closely resembles that observed in continuous FeRh films 23 and wires, 13 i.e. nearly linear with a slope of −9.1 K/T as seen in Fig.…”
Section: Chemical Composition and Crystallographysupporting
confidence: 55%
“…16 A sharp transition has been observed in a 50 nm thick FeRh (001) film grown over MgO (001), closing the loop in ∼40 K with similar shapes of the two branches, 18 while Loving et al have reported a loop over ∼300 K with a coolingdown branch significantly wider than the heating-up branch. 22 Nevertheless, a linear correlation between the transition temperature and the applied external field 13,23 is consistently observed, indicating that despite differences between the material microstructure and system dimensions, the intrinsic properties of FeRh B2 alloys dominate this first order metamagnetic transition. Despite a lot of studies on thin films with low defect density, 19,20,24,25 the study of single B2 FeRh nanomagnets is rather rare.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The electrical measurements show that changing the applied magnetic field from OOP to IP, results in a change in the T T of 6 K (figure 6(a)), which is not sufficient to explain the strong divergence in behaviour seen when comparing axial (figure 3) and tangential (figure 4). Based on the finite-element modelling simulations and previous studies [33], a laser pulse with a fluence of 4.0 mJ cm −2 , is expected to induce a temperature rise of > 150 K. As such, the excited sample will transition to the fully FM state, irrespective of field direction. However, the demagnetisation field strength as a function of angle offers a more plausible argument.…”
Section: Resistance Vs Magnetic Field Curvesmentioning
confidence: 99%
“…Despite the large body of work on FeRh thin films, the effect of lateral confinement on the transition dynamics remains under-reported. The dynamics of the FeRh phase transition have been explored with probing of the electronic [15], magnetic [31,32], and lattice [33] transformations across a range of timescales from sub-ps [15] up to ns [34,35]. It is known that the AF → FM transition mechanism differs from the reverse transition as a consequence of the different domain sizes (AF domain sizes are <100 nm, while FM domain sizes ≈1 µm) [36][37][38].…”
Section: Introductionmentioning
confidence: 99%